2021
DOI: 10.1093/ehjdh/ztab078
|View full text |Cite
|
Sign up to set email alerts
|

Detecting cardiomyopathies in pregnancy and the postpartum period with an electrocardiogram-based deep learning model

Abstract: Aims Cardiovascular disease is a major threat to maternal health, with cardiomyopathy being among the most common acquired cardiovascular diseases during pregnancy and the postpartum period. The aim of our study was to evaluate the effectiveness of an electrocardiogram (ECG)-based deep learning model in identifying cardiomyopathy during pregnancy and the postpartum period. Methods and Results We used an ECG-based deep learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Given the distinct features of pregnancy, a study was necessary to show the suitability of an ECG-based DLM for pregnant patients compared with its effectiveness for ordinary patients. In August 2021, Adedinsewo et al conducted a study at the Mayo Clinic and reported that ECG-DLM effectively detects cardiomyopathy related to pregnancy [19]. Our model achieved an AUROC of 0.877 in the external validation test (LVEF 45% or less) compared with Mayo Clinic's AUROC of 0.89 (LVEF <45%); both studies manifest excellent performance of the DLM in the pregnancy group.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Given the distinct features of pregnancy, a study was necessary to show the suitability of an ECG-based DLM for pregnant patients compared with its effectiveness for ordinary patients. In August 2021, Adedinsewo et al conducted a study at the Mayo Clinic and reported that ECG-DLM effectively detects cardiomyopathy related to pregnancy [19]. Our model achieved an AUROC of 0.877 in the external validation test (LVEF 45% or less) compared with Mayo Clinic's AUROC of 0.89 (LVEF <45%); both studies manifest excellent performance of the DLM in the pregnancy group.…”
Section: Discussionmentioning
confidence: 62%
“…However, the few, previous studies present conflicting opinions of ECGs on PPCM diagnosis. Honigberg et al [18] show that ECG has a low sensitivity for PPCM diagnosis, but a recent study from the Mayo Clinic by Adedinsewo et al [19] demonstrates the high performance of ECG-based deep learning models in left ventricular dysfunction in perinatal women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently evaluated the ability of an AI-enhanced ECG to detect cardiomyopathies during pregnancy and the postpartum period and found it to be effective (Figure 5A). 87 Other ML models specifically for use in detecting or predicting the risk for pregnancy-related disorders, such as gestational diabetes and preeclampsia, have also shown promise, albeit with limited external validation. 88 Potential AI/ digital tools that can be leveraged for screening during the peripartum period include not only the incorporation of ECG-based AI tools for cardiomyopathy detection 87 but also remote monitoring technologies for blood pressure assessments 89 and digital scales for weight assessments with automated data capture and transfer such that measurement reporting is less reliant on the patient who may also be navigating the challenges of being a new mother.…”
Section: Pregnancy and Peripartummentioning
confidence: 99%
“…87 Other ML models specifically for use in detecting or predicting the risk for pregnancy-related disorders, such as gestational diabetes and preeclampsia, have also shown promise, albeit with limited external validation. 88 Potential AI/ digital tools that can be leveraged for screening during the peripartum period include not only the incorporation of ECG-based AI tools for cardiomyopathy detection 87 but also remote monitoring technologies for blood pressure assessments 89 and digital scales for weight assessments with automated data capture and transfer such that measurement reporting is less reliant on the patient who may also be navigating the challenges of being a new mother. Data captured from these monitoring tools can be incorporated into an ML algorithm to identify uncontrolled hypertension and elevated BMI and incorporated with smartphone-based apps to provide automated educational interventions on lifestyle modification or prompts to ensure medication compliance.…”
Section: Pregnancy and Peripartummentioning
confidence: 99%